Predicting the canopy conductance to water vapor of grapevines using a biophysical model in a hot and arid climate - Egipto, Ricardo Jorge Lopes; Aquino, Arturo; Andújar, José Manuel (Frontiers in Plant Science, 2024)
Canopy conductance is a crucial factor in modelling plant transpiration and is highly responsive to water stress. The objective of this study is to develop a straightforward method for estimating canopy conductance (gc) in grapevines. To predict gc, this study combines stomatal conductance to water vapor (gsw) measurements from grapevine leaves, scaled to represent the canopy size by the leaf area index (LAI), with atmospheric variables, such as net solar radiation (Rn) and air vapor pressure deficit (VPD). The developed model was then validated by comparing its predictions with gc values calculated using the inverse of the Penman Monteith equation. The proposed model demonstrates its effectiveness in estimating the gc, with the highest root-mean-squared-error (RMSE=1.45x10 -4 m.s -1 ) being lower than the minimum gc measured in the field (gc obs=0.0005 m.s -1 ). The results of this study reveal the significant influence of both VPD and gsw on grapevine canopy conductance.